A brief note on monotonic and fatigue fracture events investigation of thin-walled tubular austenitic steel specimens via fracture surface topography analysis (FRASTA). (April 2022) - Macek, Wojciech; Sampath, Dhinakaran; Pejkowski, Łukasz; Żak, Krzysztof
Highlights: Quantitative method called fracture surface topography analysis (FRASTA) is used. FRASTA is applied to fatigue fracture of a thin-walled stainless steel tube. FRASTA has revealed fracture initiation and progression under tensile and fatigue loads. Fracture surface topography parameters are used to delineate fracture features. Abstract: The main objective of this short communication is to show the fracture progression in each loading case and complement knowledge about fracture mechanisms underpinning the tensile and fatigue performance of thin-walled tubes. For this purpose, the fracture surface topography analysis (FRASTA) method was used in the thin-walled tubular austenitic stainless-steel specimens. Two cases were analyzed: monotonic tension, and uniaxial fully-reversed fatigue. Furthermore, the fractures topographies were quantified through the profiles over their entire surfaces with the support of an optical confocal measurement system. The results showed the usefulness of the FRASTA method in identifying characteristic zones in the cracking process for the analyzed cases and motivates its development for other materials and complex loading cases.